Fibrinolytics in the treatment of complicated pneumonia in pediatrics: An integrative review (Research, Society and Development, 2024)
Introduction: Community-Acquired Pneumonia (CAP) is a significant pulmonary infection, particularly in children under five years old, with high mortality in developing countries. Severe complications, such as pleural effusion and empyema, are common and are associated with clinical deterioration and prolonged hospitalization. Objective: This study aims to conduct an integrative literature review to evaluate the indications and effectiveness of fibrinolytic therapy in cases of complicated pneumonia in pediatrics. Methodology: This study conducted an integrative literature review using the LILACS, SciELO, and MEDLINE databases via PubMed, with descriptors such as "fibrinolytics," "complicated pneumonia," "pleural effusion," and "children," considering articles published between 2020 and 2024. Results: A total of 98 articles were identified, of which 9 met the inclusion criteria and were analyzed. Discussion: Fibrinolytic therapy has the potential to reduce hospital stay and the complications associated with the treatment of pleural effusion and empyema in children. However, the heterogeneity of the data and the discrepancies in study results indicate the need for further clinical research to establish safer and more effective protocols. Conclusion: Despite advances in the treatment of complicated CAP, significant gaps in the literature still limit the full understanding of the efficacy of fibrinolytic therapy. Additional studies are needed to provide more consistent data and clear guidelines on managing these complications in pediatrics.